Content validity and internal reliability of Slovene version of Medication Administration Error Survey - Vrbnjak, Dominika (Obzornik zdravstvene nege, 2016)
Introduction: In Slovenia there is a lack of valid and reliable instruments for measuring medication administration errors. The aim of research is to determine the content validity and internal reliability of the Slovenian version of the ''Medication Administration Error Survey''. Methods: We used the translation and back translation tested the questionnaire for its content validity on the basis of an agreement of eight experts. Content validity was quantified by the content validity index and a modified Cohen kappa index. A cross-sectional design, with a convenience sample of 91 caregivers working in internal or surgical wards in two health care institutions, was used to test the internal consistency by calculating Cronbach's alpha and corrected item-total correlations. Results: 64 items showed an excellent content validity index, ranging from 0.875 to 1.000, and modified kappa index over 0.740. Two items had a content validity index 0.750 and modified kappa index 0.560. The average content validity index for three main parts of the questionnaire ranged from 0.940 to 0.959. Cronbach's alpha for these three parts ranged from 0.832 to 0.989. The corrected item-total correlations reached a required criterion for all items, except one. Discussion and conclusion: Instrument has an acceptable content validity and internal reliability, however, due to some methodological shortcomings results should be interpreted with caution. Further psychometric testing is needed.
Keywords: bolnišnice; hospitals; instruments development; oblikovanje instrumentov; pacienti; patients; psihometrične lastnosti; psychometric properties; safety; security; varnost